Encephaloduroarteriosynangiosis (EDAS) revascularization for symptomatic intracranial atherosclerotic steno-occlusive (ERSIAS) Phase-II objective performance criterion trial. Issue 6 (August 2021) - Gonzalez, Nestor R; Jiang, Hao; Lyden, Patrick; Song, Shlee; Schlick, Konrad; Dumitrascu, Oana; Quintero-Consuegra, Miguel D; Toscano, Juan F; Liebeskind, David S; Restrepo, Lucas; Rao, Neal; Hinman, Jason; et al.
Background: Intracranial atherosclerotic disease (ICAD) is one of the most challenging stroke etiologies, with frequent recurrences despite optimized medical management. Encephaloduroarteriosynangiosis (EDAS) is an indirect revascularization method that produces extra-cranial collaterals to intracranial vessels. We present the results of a phase-II trial of EDAS in intracranial atherosclerotic disease patients. Aims: To evaluate the feasibility, safety, and preliminary efficacy of EDAS in intracranial atherosclerotic disease patients. Methods: ERSIAS was a prospective objective-performance-criterion trial of EDAS plus intensive medical management (IMM) in intracranial atherosclerotic disease (ICAD) patients failing medical treatment. Primary endpoint was any stroke/death within 30-days post-surgery or stroke in the territory of the qualifying artery beyond 30 days. The primary analysis compared event rates through one year with an objective-performance-criterion based on a 10% reduction from the 20% rate in the intensive medical management arm of the stenting versus aggressive medical management for preventing recurrent stroke in intracranial stenosis trial (SAMMPRIS) in patients with poor collaterals. Event rates through two years were compared with propensity-score-matched (PSM) medically treated patients from SAMMPRIS and the carotid occlusion surgery study (COSS). Results: During a median follow-up of 24.5 months, 5 (9.6%) of 52 patients had a primary endpoint event. The primary endpoint rate at one year met the threshold for nonfutility and advancement to phase III (<10%). In the sensitivity analysis, primary endpoint event rate at two years was lower than in PSM controls, 9.6% versus 21.2% (p < 0.07). Overall, 86% of EDAS-plus-intensive medical management patients were functionally independent at last follow-up and 89% demonstrated neovascularization. There were two (3.8%) surgical complications and no intracranial hemorrhages. Conclusion: ERSIAS phase II provides evidence of safety and strong signals of efficacy of EDAS-plus-intensive medical management, supporting advancement to a seamless phase-IIb/III trial. Clinical Trial Registration: URL:https://www.clinicaltrials.gov.NCT01819597 .